Analisa Stressor Pada Ibu Hamil Primipara Terhadap Proses Persalinan - Afrino, Reki; Janah, Rahmatul (REAL in Nursing Journal, 2019)
According World Health Organization (WHO) data, maternal mortality is high. Every day, around 800 women die because of pregnancy complications childbirth in the world. Based on data Health Service in 2018 in Guguk Panjang Community Health Center, there were 647 pregnant women in Guguk Panjang Community Health Center, Bukittinggi. Therefore, this study aimed to determine The Analysis of Stressor Primipara Pregnant Women toward the Delivery Process in Guguk Panjang Community Health Center Bukittinggi.The type of this research was qualitative with descriptive phenomenology approach. It was conducted on April-May 2019. By using purposive sampling technique, 7 respondents had been chosen as the samples. The data were collected through in-depth interviews.The results of this research showed that there were three schemes gotten. First, the causes stress because internal and external factors. Then, the influences of stress because the roles of psychological and social factors. Last, there were three ways to reduce stress due to support from social factors and activities from relaxation and spiritual. In short, it can be concluded that the causes of stress, the effect of stress and how to reduce stress of primipara to prevent the inhibition of labor. Therefore, it is expected that midwives improve health promotion activities to prevent stressors in labor. Keywords               : Stressor, Primipara, Labor Experience